Severe sink-in occurrence in thermally sprayed hydroxyapatite coating - Saeed Saber-Samandari (Processing and Application of Ceramics, 2018)
The performance of orthopaedic and dental implants counts on the ability to appraise the mechanical properties of biomaterials. In the present study, nanoindentation was used to characterize the mechanical properties of thermally sprayed hydroxyapatite-coated commercial pure titanium (HA/CP-Ti). From the XRD patterns, the as-sprayed HA coating showed an inhomogeneous mixture of polycrystalline and amorphous phases along with the formation of the decomposed constituents including tricalcium phosphate (α-TCP), tetracalcium phosphate (TTCP) and calcium oxide (CaO). The SEM micrographs of HA coating indicated some incompletely melted particles on the surface of flattened droplets, where the average pore size was around 0.8 µm. After the loadunload indentation experiment, a clear severe sink-in deformation feature was observed around the residual indentation impression of the amorphous part. In contrast, pile-up only occurs during loading for the crystalline part of the coating. In addition, the crystalline part of the coating exhibited a Young’s modulus and hardness of around 120.46 and 7.91 GPa, respectively, which were almost 8 and 259% higher than that of the bare CP-Ti substrate. This is the first report on the nanoindentation characterization of the inhomogeneous mixture of various phase structures in thermally sprayed HA coatings.